2017
DOI: 10.1111/plb.12551
|View full text |Cite
|
Sign up to set email alerts
|

Temporal, but not spatial, changes in expression patterns of petal identity genes are associated with loss of papillate conical cells and the shift to bird pollination in Macaronesian Lotus (Leguminosae)

Abstract: In the generally bee-pollinated genus Lotus a group of four species have evolved bird-pollinated flowers. The floral changes in these species include altered petal orientation, shape and texture. In Lotus these characters are associated with dorsiventral petal identity, suggesting that shifts in the expression of dorsal identity genes may be involved in the evolution of bird pollination. Of particular interest is Lotus japonicus CYCLOIDEA 2 (LjCYC2), known to determine the presence of papillate conical cells o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Our results showed that the foraging behavior of visitors differed between plain and ornamented flowers, even when the visitors were of the same pollinator guild, demonstrating that floral paedomorphosis can affect the pollination strategy in Trimezieae. A similar connection between paedomorphosis and switch in pollination strategies has already been suggested for different angiosperm lineages (Guerrant, 1982; Laurent et al, 1999; Ojeda et al, 2017). In Trimezieae, profound modification of the development pathway of plain flowers is associated with suppression of floral features of ecological relevance such as glandular trichomes, hinge‐like petals, and style apex elaboration.…”
Section: Discussionsupporting
confidence: 70%
“…Our results showed that the foraging behavior of visitors differed between plain and ornamented flowers, even when the visitors were of the same pollinator guild, demonstrating that floral paedomorphosis can affect the pollination strategy in Trimezieae. A similar connection between paedomorphosis and switch in pollination strategies has already been suggested for different angiosperm lineages (Guerrant, 1982; Laurent et al, 1999; Ojeda et al, 2017). In Trimezieae, profound modification of the development pathway of plain flowers is associated with suppression of floral features of ecological relevance such as glandular trichomes, hinge‐like petals, and style apex elaboration.…”
Section: Discussionsupporting
confidence: 70%
“…For instance, the dorsalization (the acquisition of the morphology of the dorsal petal) of lateral and ventral petals in Cadia purpurea (G. Piccioli) Aiton is the result of a homeotic transformation due to an expansion of the expression domain to the lateral and ventral domains of the CYCLOIDEA gene conferring dorsal identity (Pennington et al, 2006). Similarly, the lateralization of the dorsal and ventral petals among Lotus species of the Macaronesia region have been associated with a shift in the timing of expression of the CYCLOIDEA gene responsible for lateral identity (Ojeda et al, 2017). Furthermore, specimens of Lathyrus odoratus L. with modified dorsal petals (hooded mutant, hhd) have been explained by alterations of gene expression and sequence truncation of the CYCLOIDEA dorsal identity gene, which resulted in a homeotic alteration resulting in the lateralization of the dorsal petal in this loss of function mutant (Woollacott and Cronk, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Brockington et al (2013) demonstrated that a MYB17 gene from L. japonicus could induce epidermal cell outgrowth into conical forms when expressed ectopically. However, changes in petal shape and the distribution of conical cells in the bird pollinated section of Lotus ( Rhyncholotus (Monod) D.D.Sokoloff), such that they are lost from the standard petal and located only towards the base of the abaxial wing petal surface, are associated with changes in the timing in expression of CYC2 ( Ojeda et al, 2012 , 2017 ). In L. japonicus , LjCYC2 determines petal-type within a zygomorphic flower, activating the transcription of Subgroup 9 MYB genes to promote conical cell development in the dorsal (standard) petal ( Feng et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%